Active Inference: First International Workshop, IWAI 2020, Co-located with ECML/PKDD 2020, Ghent, Belgium, September 14, 2020, Proceedings - Verbelen, Tim; Lanillos, Pablo; Buckley, Christopher L; De Boom, Cedric (Communications in Computer and Information Science, 2020)
This book constitutes the refereed proceedings of the First International Workshop on Active Inference, IWAI 2020, co-located with ECML/PKDD 2020, held in Ghent, Belgium, in September 2020. The 13 full papers along with 6 short papers were thoroughly reviewed and selected from 25 submissions. They are organized in the topical sections on active inference and continuous control; active inference and machine learning; active inference: theory and biology.